Owner Representative Decisions and Risk Drivers of Residential Project Delays - Johanes Franata Ginting; Budi Susetyo (Academia Open, 2026)
General Background: Rapid population growth in Indonesia increases housing demand and pressures residential project schedules. Specific Background: Residential projects require coordination among stakeholders, with the owner’s representative responsible for key project approvals. Knowledge Gap: The role of the owner’s representative in project time performance remains insufficiently studied. Aims: This study examines owner representative decision factors related to schedule performance using SEM-PLS, risk matrix, and SWOT analysis. Results: The model shows strong validity and reliability, with Site, Materials, and Labor identified as the main delay risks. Novelty: The study links owner decision-making with schedule deviation risks through an integrated analytical framework. Implications: Proactive decisions, early site validation, and improved material and labor management are essential to maintain schedule stability in residential construction projects. Highlights: Site conditions, material availability, and workforce factors form the dominant moderate-level delay risks. Measurement model demonstrates strong construct validity and reliability through high AVE and composite reliability values. Strategic positioning in the diversification zone supports Strength–Threats mitigation to control schedule deviation. Keywords: Website Development, Pesantren Profile, Digital Transformation, Usability, Waterfall.